CoreMap: a rapid prototyping environment for distributed reconfigurable systems. (27th January 2006) - Bobda, Christophe
We present two methods for solving the temporal partitioning problem. The first one is an enhancement of the well-known list scheduling method. The enhancement uses the so-called configuration switching to minimise the number of partitions. The second method first uses a three-dimensional spectral placement to position the modules in a three-dimensional vector space. The partitioning is done by picking components along the time-axis in increasing order of the time-coordinates. The Kernighan-Lin (KL) (Kernighan and Lin, 1970; Fiduccia and Mattheyses, 1982; Lengauer, 1990) algorithm with a modified gain function adapted to our need is then used to move the nodes of the graph from one partition to the other to insure an unidirectional partition.